Production Performance and Serum Biochemical Indices as Influenced by Lysine and Methionine Supplementation to Low Protein Diet in Vanaraja Laying Hens (Indian Journal of Animal Production and Management, 2024)
An experiment was conducted to evaluate the effect lysine and methionine supplementation to low  protein diet on production performance and serum biochemical parameters in Vanaraja laying hens.  One hundred twenty (n=120), 30-weeks old Vanaraja laying hens were randomly distributed into four  dietary treatments with three replicates in each group having 10 birds in each replicate. Four diets  were formulated with 2600 kcal/kg of metabolizable energy (ME) and 13% crude protein (CP). The  dietary treatments were: T1- diet contains 0.65% lysine and 0.28% methionine; T2- diet contains  0.70% lysine and 0.32% methionine; T3- diet contains 0.75% lysine and 0.36% methionine and T4-  diet contains 0.80% lysine and 0.40% methionine. Body weight and its changes, Hen Housed Egg  Production (HHEP), egg weight (g), egg mass (g/day), and feed conversion ratio and serum  biochemical parameters found significantly (P
Keywords: Methionine; lysine; low protein diet; serum biochemical parameters; hen